EFEKTIVITAS PELAYANAN BUS SEKOLAH GRATIS PADA DINAS PERHUBUNGAN KOTA DENPASAR - Karuni, Ni Made Nadhya; Supriliyani, Ni Wayan; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER, 2020)
ABSTRACT Denpasar School Bus is an innovative transportation service by Land Transportation Department Denpasar City in order to provide convenience for students in using public transportation to go to school. This research uses descriptive qualitative methods with data collection techniques such as interviews, observation, and documentation. The results of the research related to the effectiveness of the Free School Bus services at the Transportation Department Denpasar City were analyzed using three indicators of effectiveness from Richard M. Steers consisting of optimizing objectives, system perspectives, and stresses in terms of employee behavior in organizations that show that service from implementing School Buses Denpasar is not yet fully said to be optimal or well organized, because there are still problems with some of the indicators, which are related to facilities and infrastructure that are not optimal, limited access to applications, the lacking of employees . Keywords: Denpasar School Bus, Denpasar City Transportation Department, Effectiveness of Service